2012
DOI: 10.1111/j.1365-2753.2012.01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to abandon paper? The use of emails and the Internet for health services research – a cost‐effectiveness and qualitative study

Abstract: Researchers should consider using email invitations as a cost-effective first-line strategy to recruit patients to participate in health services research. Internet questionnaires are potentially cheaper than paper questionnaires, and the format is acceptable to many patients. However, for the time being, concurrent alternate formats need to be offered to ensure wider acceptability and to maximize response rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…It is only relatively recently that the questionnaire has taken an electronic form. Web based questionnaires have been evaluated in many studies and found to be acceptable to research participants (Kamo et al, 2011) and sometimes preferable to a paper version (Balter et al, 2005; Mathieu et al, 2012) not least to say, cost effective compared to printing and posting a paper questionnaire (Hunter et al, 2013). Interestingly, participants are more likely to complete an online questionnaire compared to a paper one (Balter et al, 2005; Kongsved et al, 2007) and whilst one might assume there could be a sampling bias between respondents to a postal questionnaire versus an equivalent online version, in one study that explored this issue, no statistical difference was found between these two methods and response rate and socio-demographic data provided (Fleming and Bowden, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is only relatively recently that the questionnaire has taken an electronic form. Web based questionnaires have been evaluated in many studies and found to be acceptable to research participants (Kamo et al, 2011) and sometimes preferable to a paper version (Balter et al, 2005; Mathieu et al, 2012) not least to say, cost effective compared to printing and posting a paper questionnaire (Hunter et al, 2013). Interestingly, participants are more likely to complete an online questionnaire compared to a paper one (Balter et al, 2005; Kongsved et al, 2007) and whilst one might assume there could be a sampling bias between respondents to a postal questionnaire versus an equivalent online version, in one study that explored this issue, no statistical difference was found between these two methods and response rate and socio-demographic data provided (Fleming and Bowden, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To increase response rates to the online surveys (Bhinder et al, 2010;Derby, Haan, & Wood, 2011;Hunter, Corcoran, Leeder, & Phelps, 2013;McCabe, Diez, Boyd, Nelson, & Weitzman, 2006;Reynolds & Stiles, 2007), potential participants were e-mailed invitations to complete the surveys, unique online links to the surveys were included in the e-mails, and participants were given the option to save a partly completed survey draft and continue answering later. Participation in surveys was tracked using an online survey platform.…”
Section: Methodsmentioning
confidence: 99%
“…Invitation to complete a survey by email have become a common data collection strategy (Bosnjak, Neubarth, Couper, Bandilla, & Kaczmirek, 2008;McCoyd & Kerson 2006). According to Hunter, Corcoran, Leeder, and Phelps (2013) and Sappleton (2013), the use of email as a data collection method allows researchers to obtain results quickly and at minimal cost. As a means of data collection, the email survey offers an increased sample size, greater sample diversity, easier access and convenience, lower costs and time investment, and many other appealing features as compared to other methods (Corley & Jansen, 2000).…”
Section: Data Collection Strategymentioning
confidence: 99%